2010
DOI: 10.1007/s13364-010-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of least cost paths for determining effects of habitat types on landscape permeability: wolves in Poland

Abstract: Determining ecological corridors is crucial for conservation efforts in fragmented habitats. Commonly employed least cost path (LCP) analysis relies on the underlying cost matrix. By using Ecological Niche Factor Analysis, we minimized the problems connected with subjective cost assessment or the use of presence/absence data. We used data on the wolf presence/absence in Poland to identify LCPs connecting patches of suitable wolf habitat, factors that influence patch occupancy, and compare LCPs between differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…In particular, it appears that westward dispersal from regions 10 and 11 has been relatively frequent. The location of these sampling regions on the western border of the established wolf range in northeastern Poland, and the relatively contiguous forest habitat in this area (Huck et al 2011) suggest that regions 10 and 11 represent a natural starting point for westward expansion (Jędrzejewski et al 2008;Huck et al 2010Huck et al , 2011. Wolves in western Poland and eastern Germany appear to represent the expanding western edge of a vast, northeastern European wolf population that primarily inhabits boreal and temperate forests and extends through the Baltic States, northern Belarus, and northwestern Russia (Pilot et al 2006(Pilot et al , 2010.…”
Section: Recolonization Of Western Poland and Eastern Germanymentioning
confidence: 95%
See 2 more Smart Citations
“…In particular, it appears that westward dispersal from regions 10 and 11 has been relatively frequent. The location of these sampling regions on the western border of the established wolf range in northeastern Poland, and the relatively contiguous forest habitat in this area (Huck et al 2011) suggest that regions 10 and 11 represent a natural starting point for westward expansion (Jędrzejewski et al 2008;Huck et al 2010Huck et al , 2011. Wolves in western Poland and eastern Germany appear to represent the expanding western edge of a vast, northeastern European wolf population that primarily inhabits boreal and temperate forests and extends through the Baltic States, northern Belarus, and northwestern Russia (Pilot et al 2006(Pilot et al , 2010.…”
Section: Recolonization Of Western Poland and Eastern Germanymentioning
confidence: 95%
“…In southern Poland, wolves occurred only in a narrow belt of \100 km, whereas in northern Poland stable wolf populations persist more than 200 km from the continuous wolf range (Jędrzejewski et al 2004(Jędrzejewski et al , 2005a. Huck et al (2010Huck et al ( , 2011 analysed dispersal costs among patches of wolf habitat and modeled dispersal corridors in Poland, and found that dispersal from the Carpathians to any other patch would be much more costly than dispersal among other regions of the country. Densely populated and urbanized areas in southern Poland along the Carpathians may act as a serious barrier to wolf movement and limit wolf dispersal (Huck et al 2011).…”
Section: Factors That Could Maintain Divisions Between Genetically DImentioning
confidence: 99%
See 1 more Smart Citation
“…Landscape resistance is often based on habitat suitability indices or expert opinion, where high habitat suitability is interpreted as low resistance or cost (Sawyer et al 2011;Poor et al 2012;Zeller et al 2012). Unfortunately, many examples of cost-based corridor model applications have weaknesses, for example the use of habitat selection information that is generalized from the literature (e.g., LaRue and Nielsen 2008;Li et al 2010;Huck et al 2011) (despite being locality specific and often variable across sites and thus not generalizable ;Fahrig 2007) and the cost-based models themselves unrealistically assume an animal either has complete knowledge of the landscape (e.g., least cost path analysis; Adriaensen et al 2003) or no memory of the landscape (i.e., random walkers; e.g., McRae et al 2008). Most importantly, despite intending to predict and facilitate animal movements, most corridor studies do not directly incorporate animal behavior into their models (Chetkiewicz et al 2006;Beier et al 2008;Sawyer et al 2011;Zeller et al 2012), and only a few have compared their model predictions with movement data (Driezen et al 2007;Poor et al 2012;Walpole et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Even now, after decades of human infrastructure development, a habitat suitability model has revealed that there are plenty of good habitats for wolves in WPL (39,000 km 2 , 63% of all habitats available in the country), which could host up to 790 wolves (Jędrzejewski et al, 2008). These habitats are quite well connected by network of ecological corridors which allow dispersal of wolves between EPL and WPL, in both directions (Jędrzejewski et al, 2009;Schede et al, 2010;Huck et al, 2010Huck et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%